Attention-deficit/hyperactivity disorder medication consumption in 64 countries and regions from 2015 to 2019: a longitudinal study. (April 2023) - Chan, Adrienne Y.L.; Ma, Tian-Tian; Lau, Wallis C.Y.; Ip, Patrick; Coghill, David; Gao, Le; Jani, Yogini H.; Hsia, Yingfen; Wei, Li; Taxis, Katja; Simonoff, Emily; Taylor, David; et al.
Summary: Background: Timely recognition and appropriate treatment of attention-deficit/hyperactivity disorder (ADHD) are essential to enhance long-term outcomes of individuals with ADHD. This study aimed to evaluate the multinational trends and patterns of ADHD medication consumption. Methods: In this longitudinal trend study, we used pharmaceutical sales data of ADHD medication from the IQVIA-Multinational Integrated Data Analysis System between 2015 and 2019, covering 64 countries across the world. Consumption rates of ADHD medication were expressed as defined daily dose per 1000 child and adolescent inhabitants (aged 5–19) per day (DDD/TID). Linear mixed models were used to estimate the multinational, regional, and income level trend changes. Findings: The results showed that multinational ADHD medication consumption increased by +9.72% (95% confidence interval [CI], +6.25%, +13.31%) per year, from 1.19 DDD/TID in 2015 to 1.43 DDD/TID in 2019 across the 64 countries with marked differences between geographical locations. When stratified by countries' income levels, increases in ADHD medication consumption were observed in high-income countries but not in middle-income countries. In 2019, the pooled consumption rates of ADHD medication were 6.39 DDD/TID (95% CI, 4.63, 8.84) in high-income countries, 0.37 DDD/TID (95% CI, 0.23, 0.58) in upper-middle-income countries and 0.02 DDD/TID (95% CI, 0.01, 0.05) in lower-middle-income countries. Interpretation: Current ADHD prevalence estimates and rates of ADHD medication consumption in most middle-income countries are lower than the global epidemiological prevalence. It is therefore imperative to evaluate the potential barriers to diagnosis and treatment in these countries to minimise the risk of negative outcomes from undiagnosed and untreated ADHD. Funding: This project was funded by a grant from the Hong Kong Research Grants Council Collaborative Research Fund (project number C7009-19G ).